Studi Komparasi Penerapan Science, Technology, Engineering, And Mathematics (STEM) di Dunia Pendidikan Malaysia Dan Indonesia Dalam Meningkatkan Literasi Teknologi Sebagai Penunjang Revolusi Industri - Firdausia, Fadliyanti; Effendi, Muhammad Idris; Chisbiyah, Lismi Animatul (Universitas Nahdlatul Ulama Blitar, 2025)
Education is one of the forms of quality Human Resources (HR). By applying the STEM approach in education, there are complex treatments that apply to the educational process in terms of technology, science, engineering and mathematics. The Study Literature Review (SLR) method was applied by researchers by analyzing relevant topics from 75 articles found but selected according to the needs of related topics, there were approximately 30 relevant articles that had been reviewed so the findings from this comparison which aims to find out STEM in Malaysian and Indonesian education, show that both countries basically have advantages and disadvantages regarding the application of STEM in each country in accordance with the country's policies, of course. However, the application of STEM in Malaysia is more inclined and has generally been realized in education in that country.